Determinants of maximal oxygen utilisation - Wagner, P. (1998)
Author gives a basic (but very clear lecture) on the physiology of oxygen uptake transport and utilisation. He discussed: 1. What determines VO2 max 2. Sea level adaptations to sea level training 3. Additional influences of altitude.